सामान्य संदर्भ संधार (भाषा, साहित्य, शिक्षा के उद्देश्य) - (:unkn) unknown (My University, 2012)
This volume would help all those who are working in the areas of teaching, learning, evaluation, syllabus construction, and tool making.
General Frame of Reference (Language, Literature, Objectives of Education)
Keywords: Hindi; English